Enhancing Scientific Writing Proficiency Through the Problem-Based Learning Model: A Novel Approach in Academic Education - Erda Wati; Gunawan Suryoputro; Ade Hikmat (AL-ISHLAH: Jurnal Pendidikan, 2025)
Writing scientific papers is a critical academic skill that students must develop to express ideas derived from observation, research, or analysis in a structured and methodical manner. However, students often face challenges in mastering this skill. This study investigates the effectiveness of the Problem-Based Learning (PBL) model in improving students’ ability to write scientific papers. The research employed Classroom Action Research (CAR), implemented in two cycles at MA Mizanul Ulum YW UMI Sanrobone. Each cycle followed the stages of planning, implementation, observation, and reflection. The study involved student participants who were observed through activity sheets and assessed through writing assignments. Data were analyzed using both qualitative and quantitative descriptive techniques. Findings indicate a notable improvement in students' scientific writing performance after the implementation of the PBL model. In Cycle I, the average student score was 64, indicating that most had not yet met the minimum competency standard. After refining the instructional approach in Cycle II, the average score increased significantly to 81, demonstrating that all students achieved the required level of competence. The results suggest that the PBL model fosters student engagement and enhances their ability to develop and organize scientific content effectively. By actively involving students in problem-solving tasks, the model promotes deeper understanding and better writing outcomes. Implementing the PBL approach significantly improved students’ scientific writing skills and learning outcomes. This model is recommended for broader application in similar educational settings.